Fundamentals of telecommunication networks - Saadwi, Tarek N. (Wiley series in telecommunications and signal processing., 1994)
Comprehensive, authoritative, practical-an essential guide to the design and operation of telecommunication networks The past decade has seen what can only be described as an evolutionary leap in the field of telecommunication networks. The penetration of data networks, the emergence of the integrated services digital network (ISDN) and Broadband ISDN, and the development of fast packet switching, are just some of the dramatic developments that have emerged over the past few years alone. This book was designed to function as a practical introduction to the core concepts, techniques, and methodologies underlying each of these developments and common to the design and operation of all forms of existing telecommunications networks. Key topics covered include: The physical layer of the OSI reference model Performance evaluation techniques Queueing theory fundamentals and their applications to networks Layers 2 and 3 of the OSI reference model - including an in-depth discussion of protocol standards,routing algorithms, and flow and congestion control techniques LAN theory, standards, and technology and multiple access communications techniques Network interconnection and the transport layer ISDN, Broadband ISDN, and fast packet switching theory and architectureFundamentals of Telecommunication Networks is an invaluable resource for systems developers, engineers, and managers responsible for dealing with telecommunications networks and systems.